Pengaruh Transfer Pricing, Karakter Eksekutif, dan Koneksi Politik Terhadap Tax Avoidance - Santi Haztania; Tri Utami Lestari (Cakrawala Repositori IMWI, 2023)
Tax is the largest contribution to the state made by taxpayers and is used as a state necessity for the prosperity of the people. For companies, tax is a profit deduction element which can be a factor that can harm the company. The difference in interests can lead to conflicts such as taxpayer non-compliance which will have an impact on the company's efforts to minimize taxes. This effort is carried out by carrying out a tax avoidance scheme, one of the tax avoidance efforts that is often carried out legally and safely is tax avoidance. Tax avoidance is a legal tax avoidance effort carried out by utilizing the loopholes (gray area) in the applicable tax laws and regulations with the aim of minimizing the amount of tax payable. The measurement of tax avoidance in this study is using the Cash Effective Taxes Rate (CETR) proxy. This study was conducted to analyze the effect of transfer pricing, executive character, and political connections on tax avoidance simultaneously and partially in manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The population in this study is manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The sample selection technique used was purposive sampling. The sample obtained was 35 companies, so the number of observations in this study for 3 (three) years was 105 observation data. The data analysis method in this study was analyzed using descriptive statistics and panel data regression with the help of EViews 10 software. The results of this study indicate that simultaneously transfer pricing, executive character, and political connections affect tax avoidance. Partially, transfer pricing has no effect on tax avoidance, while executive character and political connections affect tax avoidance.